EVALUATION OF DRUG PLANNING AND PROCUREMENT IN PHARMACY DEPARTEMENT OF SEMARANG HEALTH AGENCY - Fitri Pratiwi; Iwan Dwiprahasto; Endang Budiarti (Faculty of Pharmacy, Universitas Gadjah Mada)
The Pharmacy Departement of Semarang Health Agency is where a management of drugs taking place inSemarang. In order to provide quality health care, we need to evaluate the phases in the planning and procurementof drugs as well as the match between the planning and procurement. Data was collected retrospectively with descriptive observations and the calculation of indicators of the planningand procurement where the obtained data are described and compared with the results of interviews.The results indicated that drug planning using APBD II source of funding was done with consumption method.The planning was done twice, first planning for budget submission and second planning for budget adjustments.Inappropriateness in drug planning and procurement, was not influence by limitations of funding, but caused bydrug procurement that held once each year. This method of drugs procurement could not avoid drgug unavaibility, and delay of drugs delivery and unmet need for drugs by the winner of tender even if sufficient funds was available. Keywords: drug planning, drug procurement, The Pharmacy Departement of Semarang Health Agency.